(untitled) (Journal of Educational Management, 2012)
The Investors in People study of the Mathematics Department of Merton College was undertaken in November 2008 to determine the extent to which the Mathematics Department met the indicators of the new Standard introduced by Investors in People UK in 2005 in the face of the changes that were being implemented in the whole college. The study involved 14 out of the 23 staff in the department. The main instruments used were structured interview schedules, albeit relevant documents were also examined. The key finding was that generally, managers were able to demonstrate an understanding of how to count the costs and benefits of learning and development, and the latter’s impact on the performance of individuals in the mathematics Department. It was recommended that the Policy Team of the college should develop an Action Plan to address some of the key issues identified in the study.